Book producers’ comments on text-organisation in early 16th-century English printed paratexts - Varila Mari-Liisa (John Benjamins Publishing Company, 2022)
This chapter focuses on book producers' metadiscourse related to text-organisation in 16th-century English printed paratexts. Paratexts offered authors, translators, and printers a convenient space for instructing the reader in navigating the contents of the book at hand. Choices related to text-organisation were occasionally highlighted on the title-page and described in more detail in prefaces or letters to the reader. In this chapter, I examine title-pages and prefaces to find out how book producers justified and clarified their methods of structuring text and information and whether text-organisation was used as a selling point in the early period of print in England.
The Dynamics of Text and Framing Phenomena. Historical approaches to paratext and metadiscourse in English